Processing, Analyzing And Testing Quantitative Research Hypotheses With Smartpls Software3 - Martinus Duryadi (Lembaga Pengembangan Kinerja Dosen, 2024)
The method used in this paper is seen as the nature of exploration as applied research, the nature of the explanation of non-causality research, while the method used is qualitative. The purpose of this paper is to introduce statistical computer software. There are many computer statistics software, the author introduces SmartPLS3. SmartPLS3, compared to other computer statistical software; If used to analyze linear regression, multiple regression, especially path analysis models, has advantages. In the path analysis research model, SmartPLS3 is superior when compared to SPSS. If analyzing using SPSS to test hypotheses with moderation variables or through mediation variables, it is necessary to calculate the value of the regression coefficient using the Sobel test. The path analysis research moderation model, mediation model and combined model of mediation moderation (modmed) if analyzed using SmartPLS3 only needs to juxtapose the results of the analysis in the direct influence, moderation effect (in the path coefficient table), and in the indirect influence table (table specific indirect effect); Based on hypothesis test criteria with moderation or through mediation variables.